"They will judge you more like a parent instead of like a health practitioner": Perceptions and preferences of young people regarding sexual and reproductive health services in Southwest Nigeria - Olujide Arije; Tintswalo Hlungwani; Jason Madan (Elsevier, 2022)
Adolescents and young people (AYP) experience many barriers in the utilization of sexual and reproductive health (SRH) services. These barriers can be cultural, structural, personal or health worker-related. In this study, we explored the perceptions and preferences of AYP in receiving SRH services at public health facilities in a Nigerian setting. We conducted 16 focus group discussion (FGD) sessions with adolescents and young people allowing for maximum variation by sex (male, female), age (15-19 years and 20-24 years), and marital status (married and unmarried). We applied a thematic framework analysis to explore the data collected. Our findings included both positive and negative attitudes of health workers at public health facilities, non-involvement of AYP in activities relating to the planning, implementation, or evaluation of SRH programs for AYP, and non-awareness among AYP of some of the rights that AYP have with respect to SRH services in public health facilities. Many participants preferred younger health workers or those living within their neighborhood. Some older health workers were said to often act as (strict) parents, not health workers. We conclude that the role ascribed to 'neighborhood' nurses in this study is instructive and deserves more attention. Also, there is a need to increase the awareness of the young people about the type of SRH services they can obtain in the public health facilities, as well as, a need for health workers to be trained and retrained in providing SRH services to AYP.